2008
DOI: 10.1007/s10494-008-9146-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Explicit Algebraic Reynolds Stress Model within a Hybrid LES–RANS Method

Abstract: Large-eddy simulations (LES) still suffer from extremely large resources required for the resolution of the near-wall region, especially for high-Re flows. That is the main motivation for setting up hybrid LES-RANS methods. Meanwhile a variety of different hybrid concepts were proposed mostly relying on linear eddyviscosity models. In the present study a hybrid approach based on an explicit algebraic Reynolds stress model (EARSM) is suggested. The model is applied in the RANS mode with the aim of accounting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In order to better account for the anisotropy emerging especially in the near-wall region, in [11] the description of the nearwall region was enhanced by the introduction of the explicit algebraic Reynolds stress model (EARSM) proposed by Wallin and Johansson [12]. It represents a compromise between the too expensive full RSMs and classical linear eddy-viscosity models based on the Boussinesq approximation not capable to account for the stress anisotropy.…”
Section: Unified Les-urans Methodology With Soft Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…In order to better account for the anisotropy emerging especially in the near-wall region, in [11] the description of the nearwall region was enhanced by the introduction of the explicit algebraic Reynolds stress model (EARSM) proposed by Wallin and Johansson [12]. It represents a compromise between the too expensive full RSMs and classical linear eddy-viscosity models based on the Boussinesq approximation not capable to account for the stress anisotropy.…”
Section: Unified Les-urans Methodology With Soft Interfacementioning
confidence: 99%
“…If this quantity is below a user-defined value, the method works in URANS mode, otherwise the LES mode is applied. The influence of the location of the interface on the outcome of the hybrid predictions was studied in detail [9,11,14]. It was found that the results are not strongly depending on the chosen location as long as it is positioned in the log-layer region.…”
Section: Unified Les-urans Methodology With Soft Interfacementioning
confidence: 99%
“…One of the first studies comparing the performance of linear and non-linear hybrid models for the periodic hills was performed by Jaffrézic and Breuer [36]. No significant differences between the linear and non-linear hybrid models were observed for the grids tested.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers used two-equation models in RANS regions such as k − ε or k − ω in order to construct the hybrid RANS/LES model (Dejoan & Schiestel, 2001;Menter, Kuntz, & Langtry, 2003). An explicit algebraic Reynolds stress model was employed in the RANS region in Jaffrezic and Breuer (2008). The second aspect concerns how the LES-RANS interface is defined.…”
Section: Introductionmentioning
confidence: 99%